Nutrition-Sensitive Deltaic Agri-Food Systems - Sokchea, Moeun; Thy, Or (WorldFish, 2024)
The Nutrition Sensitive Agri-Food System intervention focuses largely on (i) capacity building related to agricultural techniques including nutrition, integrated homestead production, chicken raising and fish raising to demonstration farmers, teachers and students of two primary schools, relevant government stakeholders at local and provincial levels, (ii) stakeholder engagement to mobilize and support the implementation and dissemination of results and materials of the NSAFS pilot and (iii) evidence- based documentation to guide intervention design that contributes more effectively improving nutrition-sensitive agri- food systems in the Mekong Delta.